Classroom ventilation and indoor air quality—results from the FRESH intervention study. (4th August 2015) - Rosbach, J.; Krop, E.; Vonk, M.; van Ginkel, J.; Meliefste, C.; de Wind, S.; Gehring, U.; Brunekreef, B.
Abstract: Inadequate ventilation of classrooms may lead to increased concentrations of pollutants generated indoors in schools. The FRESH study, on the effects of increased classroom ventilation on indoor air quality, was performed in 18 naturally ventilated classrooms of 17 primary schools in the Netherlands during the heating seasons of 2010–2012. In 12 classrooms, ventilation was increased to targeted CO2 concentrations of 800 or 1200 ppm, using a temporary CO2 controlled mechanical ventilation system. Six classrooms were included as controls. In each classroom, data on endotoxin, β (1, 3)‐glucans, and particles with diameters of <10  μ m (PM10 ) and <2.5  μ m (PM2.5 ) and nitrogen dioxide (NO2 ) were collected during three consecutive weeks. Associations between the intervention and these measured indoor air pollution levels were assessed using mixed models, with random classroom effects. The intervention lowered endotoxin and β (1, 3)‐glucan levels and PM10 concentrations significantly. PM10 for instance was reduced by 25  μ g/m³ (95% confidence interval 13–38  μ g/m³) from 54  μ g/m³ at maximum ventilation rate. No significant differences were found between the two ventilation settings. Concentrations of PM2.5 and NO2 were not affected by the intervention. Our results provide evidence that increasing classroom ventilation is effective in decreasing the concentrations of some indoor‐generated pollutants.